1993
DOI: 10.1029/92ja00716
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of ion conics along the field line from EXOS D observations

Abstract: The altitude dependence of ion conics is investigated by using EXOS D observations on the dayside below 10,000 km altitude. The cone angle of ion conics tends to decrease with increasing altitude, but not so much as expected from a simple adiabatic model. The conic temperature, on the other hand, tends to increase with increasing altitude. The occurrence frequency of ion conics increases with altitude below 6000 km but is approximately constant above 6000 km. The appearance of newly born conics and the extinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…Peterson et al (1992) found that the average pitch angle of standard ion conics (`restricted' conics in their paper) shows a less signi®cant variation than expected from the conservation of the ®rst invariant at DE-1 altitudes (8000±20 000 km). Miyake et al (1993) showed similar changes of conic angle as well as the increase of energy of ion conics with altitudes in Exos-D observations at 10 000 km. It was also revealed that a large fraction of elevated conics can be explained by height-integrated perpendicular energization of ion conics (Temerin, 1986;Miyake et al, 1996).…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Peterson et al (1992) found that the average pitch angle of standard ion conics (`restricted' conics in their paper) shows a less signi®cant variation than expected from the conservation of the ®rst invariant at DE-1 altitudes (8000±20 000 km). Miyake et al (1993) showed similar changes of conic angle as well as the increase of energy of ion conics with altitudes in Exos-D observations at 10 000 km. It was also revealed that a large fraction of elevated conics can be explained by height-integrated perpendicular energization of ion conics (Temerin, 1986;Miyake et al, 1996).…”
Section: Introductionsupporting
confidence: 52%
“…There have been several reports on occurrence frequencies of ion conics based on satellite observations (Gorney et al, 1981;Yau et al, 1984;Kondo et al, 1990;Thelin et al, 1990;Peterson et al, 1992;Miyake et al, 1993Miyake et al, , 1996. Most of them, however, did not examine the quantitative relationship of the observed occurrences between ion conics with di erent conic angles and at di erent altitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That would seem to allow for greatly varying acceleration rates as well as broad ion pitch angle distributions. In fact, it is a vision that has been prompted by the frequent observations over the last 30 years of transversely accelerated ions, and it is one that is specifically consistent, superficially at least, with published statistics on the altitude dependence of ''conical'' ion velocity distributions [e.g., Peterson et al, 1992;Miyake et al, 1993Miyake et al, , 1996. However, a smoothly progressing form of acceleration alone cannot explain the occasional observation [Lennartsson, 2003] of azimuthally collimated and monoenergetic keV O + ions at 90°pitch angle at high altitude (R $ 6 R E ).…”
Section: Discussionmentioning
confidence: 83%
“…Such a mechanism may involve both transverse ion acceleration, creating ''newly born conics'' in the parlance of Miyake et al [1993], and the parallel kind. A random-type, narrow-scale (filaments) mechanism to fit that mold is outlined by Lennartsson [2003], although its specific purpose is to help explain the collocation of transversely accelerated H + , He + , and O + ions with transient bursts of hot H + ions from the near-midnight tail, rather than with cusp ion bursts.…”
Section: Discussionmentioning
confidence: 99%